Integrasi Teknologi dan Manajemen Inovasi Pembelajaran - Puput Puspito Rini (Jurnal Ilmiah Pendidikan dan Keislaman, 2024)
Technology integration in education has become a core component of the transformation of global learning systems, situated at the intersection of educational science, information technology, and innovation management, making it relevant for policymakers, practitioners, and contemporary researchers.This study aims to analyze technology integration and learning innovation management through a systematic review of integration models, teacher digital competencies, team-based leadership, the dynamics of technology-based learning spaces, and their relevance to sustainability and adaptive sectoral innovation.The method used is a Systematic Literature Review (SLR), designed to identify, evaluate, and synthesize scientific evidence in a systematic, transparent, and replicable manner to minimize bias and generate conclusions based on comprehensive scientific evidence.The review of ten articles yielded four main categories: technology integration models and frameworks using TPACK-SAMR and TIQS; leadership, teacher competencies, and human resource factors as determinants of innovation; technology-based learning spaces and organizational transformation in the context of Society 5.0; and technology integration in sustainability and green sectoral innovation in SMEs.The study concluded that the success of technology integration is determined by the quality of the pedagogical framework and institutional support, teachers' digital competence as the main determinant, systemic-multidimensional transformation of the learning ecosystem, and a local context-based green innovation orientation with communication technology as a strategic lever for sectoral sustainability.